Beyond Blame: Challenging the Myths and Inequities That Compromise Academic Mothers’ Success - Martin, BettyAnn (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
The hardships encountered by mothers in academe are compounded by certain culturalmyths that define the social perception of women’s roles in the realms of both maternalpractice and academic work. Such myths enable inequity and allow institutions toremain ignorant regarding their responsibility for the reproduction of such inequities.Indeed, prejudice regarding mothers’ perceived level of professional dedication andproductivity is particularly difficult to eradicate, as are misconceptions surroundingissues of freedom and responsibility related to women’s reproductive choices. As aresult, a culture of mother blame has flourished that encourages women to admonishthemselves for inadequacies related to both maternal practice and academic work.Through personal narrative and recourse to Anne-Marie Slaughter’s controversialessay, “Why Women Still Can’t Have it All,” this article examines the myths informingsocial understandings of academic motherhood; challenges the meanings that are madeand perpetuated by these misconceptions, which ultimately define academic mothers’experiences; and, strategizes possible solutions to women’s struggle to reconcile theirlives as mothers with their work as academics by positing, in particular, the valueand applicability of maternal intelligences, such as empathy and innovation, beyondthe domestic sphere. Ultimately, this article considers maternal ways of knowing asa site of wisdom and experiential knowledge that transcends prescriptive notions ofacademic productivity and attempts to heal the disjunction between women’s maternaland academic labours by affirming the connection between who they are and what theydo. Finally, by sharing the story of my own journey to a sustainable and expandeddefinition of academic motherhood, I hope to inspire others to share their stories and,thereby, encourage constructive dialogue as well as social and institutional reform.